(3GdfgGjI aj GdcfGjIs - (3YHO Gdedc Hf eMeO Hf ESeGYjd, CHh efUhQ GdKYGdHj,J (B429 (3g` s ((3eMeO YRGdOjf Hf eMeO GdeMhdj GdTGaYj s)
(3ChdgG (B:s
(3Yhfc Gddge Ydi TcQ fYeJc Ke Ef gPG cJGH Naja GdMLe, Kbjd GdhRf, UZjQ GdMLe s
(3BNQgG (B:s
(3jYQV dSdjeGf HCfg cGf fUQGfjkG, hcGf jJge (B((3HeeGdFI(B) (3GdfUGQi hGddg JYGdi CYde s
(3Cdag aj fjSGHhQ SfI (B400 (3g`` hQJHg Ydi SHYI CHhGHs
(3hHgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B163s
Keywords: (3GdCOHs